2022
DOI: 10.1039/d1ew00930c
|View full text |Cite
|
Sign up to set email alerts
|

Performance of AnMBRs treating low strength wastewater with different carbon sources at decreasing HRTs and its linkage to Methanosaeta with high specific affinity

Abstract: Minimum hydraulic retention time needs to be considered to avoid methanogenesis inhibition for complex substrates in anaerobic membrane bioreactor for low-strength wastewater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…87 Furthermore, several techniques including preconcentration of wastewater, culturing psychrophilic-adapted methanogens and enhancing the OLR are suggested for operating AnMBRs under psychrophilic conditions. 85,88,89 In order to further understand the microbial behaviour, many scientists analysed the effect of HRT. They showed that an increased amount of hydrogenotrophic methanogens was witnessed with the decrease in HRT.…”
Section: Recovery Of the Fouled Membranementioning
confidence: 99%
“…87 Furthermore, several techniques including preconcentration of wastewater, culturing psychrophilic-adapted methanogens and enhancing the OLR are suggested for operating AnMBRs under psychrophilic conditions. 85,88,89 In order to further understand the microbial behaviour, many scientists analysed the effect of HRT. They showed that an increased amount of hydrogenotrophic methanogens was witnessed with the decrease in HRT.…”
Section: Recovery Of the Fouled Membranementioning
confidence: 99%